2023
DOI: 10.1136/archdischild-2022-324506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early childhood development interventions delivered by healthcare providers to improve cognitive outcomes in children at 0–36 months: a systematic review and meta-analysis

Abstract: ObjectiveTo determine the effect of early childhood development interventions delivered by healthcare providers (HCP-ECD) on child cognition and maternal mental health.DesignSystematic review, meta-analysis.SettingHealthcare setting or home.ParticipantsInfants under 1 month of age.InterventionsHCP-ECD interventions that supported responsive caregiving, early learning and motor stimulation. MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Health Technology Assessment Database, Database of Abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…Various studies have shown that children from disadvantaged backgrounds who received early child development (ECD) interventions are more likely to achieve academic success, be socially and emotionally stable, and be economically productive in adulthood (Gertler et al, 2014; S. Grantham-McGregor, 2015; Woodhead, Ames, & Streuli, 2009). A number of systematic reviews and meta-analysis also confirmed the effectiveness of ECD interventions for improving the developmental status of children in LMICs when implemented by caregivers (Jeong, Franchett, Ramos de Oliveira, Rehmani, & Yousafzai, 2021) and healthcare providers (Hirve et al, 2023). For these reasons, ECD interventions are considered one of the most cost-effective strategies for reducing inequalities in LMIC (Engle et al, 2011; Irwin, Siddiqi, & Hertzman, 2007).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Various studies have shown that children from disadvantaged backgrounds who received early child development (ECD) interventions are more likely to achieve academic success, be socially and emotionally stable, and be economically productive in adulthood (Gertler et al, 2014; S. Grantham-McGregor, 2015; Woodhead, Ames, & Streuli, 2009). A number of systematic reviews and meta-analysis also confirmed the effectiveness of ECD interventions for improving the developmental status of children in LMICs when implemented by caregivers (Jeong, Franchett, Ramos de Oliveira, Rehmani, & Yousafzai, 2021) and healthcare providers (Hirve et al, 2023). For these reasons, ECD interventions are considered one of the most cost-effective strategies for reducing inequalities in LMIC (Engle et al, 2011; Irwin, Siddiqi, & Hertzman, 2007).…”
Section: Introductionmentioning
confidence: 82%
“…Grantham-McGregor, 2015;Woodhead, Ames, & Streuli, 2009). A number of systematic reviews and meta-analysis also confirmed the effectiveness of ECD interventions for improving the developmental status of children in LMICs when implemented by caregivers (Jeong, Franchett, Ramos de Oliveira, Rehmani, & Yousafzai, 2021) and healthcare providers (Hirve et al, 2023). For these reasons, ECD interventions are considered one of the most cost-effective strategies for reducing inequalities in LMIC (Engle et al, 2011;Irwin, Siddiqi, & Hertzman, 2007).…”
Section: Introductionmentioning
confidence: 98%